The clinical value of PERCIST to predict tumour response and prognosis of patients with oesophageal cancer treated by neoadjuvant chemoradiotherapy. Issue 1 (January 2020) - Nakajo, M.; Kitajima, K.; Kaida, H.; Morita, T.; Minamimoto, R.; Ishibashi, M.; Yoshiura, T.
Abstract : AIM: To examine whether Positron Emission Tomography Response Criteria in Solid Tumours (PERCIST) is useful to predict tumour response and prognosis of patients with oesophageal cancer who received neoadjuvant chemoradiotherapy (NACRT) followed by surgery. MATERIALS AND METHODS: This multicentre retrospective study included 60 patients with oesophageal cancer who underwent 2-[ 18 F]-fluoro-2-deoxy-d- glucose positron-emission tomography/computed tomography ( 18 F-FDG-PET/CT) before and after NACRT prior to surgery from January 2007 and June 2016. The correlation between pathological response and PERCIST was assessed by χ 2 test. The prognostic significance was assessed by the Kaplan–Meier method and Cox regression analysis. RESULTS: There were 30 responders and 30 non-responders pathologically. The complete metabolic response (CMR), partial metabolic response (PMR), stable metabolic disease (SMD), and progressive metabolic disease (PMD) were seen in 22, 29, seven, and two patients, respectively. There was a significant correlation between pathological response and PERCIST ( p <0.001). Forty patients showed eventual progression, and 20 patients were alive without progression between the start of NACRT and last clinical follow-up (median follow-up period; 27 months [range, 3–107]). Pathological stage and PERCIST were significant for progression-free survival (PFS; p =0.044 and 0.006, respectively) and also significant for overall survival (OS; p =0.009 and 0.001, respectively) at univariate analysis. Pathological lymph node staging was also significant for OS at univariate analysis ( p =0.018). At multivariate analysis, PERCIST remained significant and independent for PFS (hazard ratio [HR]: 1.59, p =0.046) and OS (HR: 1.82, p =0.008). CONCLUSION: PERCIST may be useful for predicting tumour response and prognosis of patients with oesophageal cancer who received NACRT. Highlights: There is a significant correlation between pathologic response and PERCIST on NACRT. PERCIST is an independent factor for PFS an OS of patients with oesophageal cancer. PERCIST is useful for predicting prognosis in oesophageal cancer received NACRT.